mcnishtia8
mcnishtia8
12-03-2021
Mathematics
contestada
h(x) = 3x-2 then h(-6) =
Respuesta :
greenforestaz
greenforestaz
13-03-2021
Step-by-step explanation:
step 1. h(-6) = 3(-6) - 2
step 2. h(-6) = -18 - 2
step 3. h(-6) = -20.
Answer Link
VER TODAS LAS RESPUESTAS ( 54+ )
Otras preguntas
if x = -2 is a zero of the polynomial function f(x) = 2x^3 +9x^2-8x-36 which of the following is another zero if f(x)
What is measured in the radiocarbon dating of organic materials?
How do I make Dank memes
A known population of a heat resistant spoilage microorganism is added to a food product. what might be going on?
Which of the following monomers would be used to make the double helix of a DNA molecule
Solve the system of equations. y=x+5 y=x2+5x−7
Line JK passes through points J(–3, 11) and K(1, –3). What is the equation of line JK in standard form?
Visible light is a range of _____ energy EM waves in the electromagnetic spectrum that the human eye can see. a.zero b.high c.low d.medium
Which property of addition is shown in the equation below? c + di + 0 + 0i = c + di commutative property inverse property identity property associative pr
a pillow is .05 centimeters. How much will it be in meters?